Methods and applications of sample size calculation and recalculation in clinical trials - Kieser, Meinhard (Springer Series in Pharmaceutical Statistics, 2020)
Part I: Basics -- Chapter 1- Introduction -- Chapter 2 - Statistical test and sample size calculation -- Part II : Sample size calculation -- Chapter 3 - Comparison of two groups for normally distributed outcomes and test for difference or superiority.-Chapter 4 - Comparison of two groups for continuous and ordered categorical outcomes and test for difference or superiority -- Chapter 5 - Comparison of two groups for binary outcomes and test for difference and superiority -- Chapter 6 - Comparison of two groups for time-to-event outcomes and test for differences or superiority -- Chapter 7 - Comparison of more than two groups and test for difference -- Chapter 8 - Comparison of two groups and test for non-inferiority -- Chapter 9 - Comparison of three groups in the gold standard non-inferiority design -- Chapter 10 - Comparison of two groups for normally distributed outcomes and test for equivalence -- Chapter 11 - Multiple comparisons -- Chapter 12 - Assessment of safety -- Chapter 13 - Cluster-randomized trials -- Chapter 14 - Multi-regional trials -- Chapter 15 - Integrated planning of phase II/III drug development programs -- Chapter 16 - Simulation-based sample size calculation -- Part III: Sample size recalculation -- Chapter 17 – Background -- Part IIIA: Blinded sample size recalculation in internal pilot study designs -- Chapter 18 - Background and notation -- Chapter 19 - A general approach for controlling the type I error rate for blinded sample size recalculation.-Chapter 20 - Comparison of two groups for normally distributed outcomes and test for difference or superiority -- Chapter 21 - Comparison of two groups for binary outcomes and test for difference or superiority -- Chapter 22 - Comparison of two groups for normally distributed outcomes and test for non-inferiority -- Chapter 23 - Comparison of two groups for binary outcomes and test for non-inferiority -- Chapter 24 - Comparison of two groups for normally distributed outcomes and test for equivalence.-Chapter 25 - Regulatory and operational aspects -- Chapter 26 - Concluding remarks.-Part IIIB: Unblinded sample size recalculation in adaptive designs -- Chapter 27 - Background and notation -- Chapter 28 - Sample size recalculation based on conditional power -- Chapter 29 - Sample size recalculation by optimization -- Chapter 30 - Regulatory and operational aspects -- Chapter 31 - Concluding remarks.